Are we taking it too far by blaming fast food restaurants for obesity? When is it individual responsibility? (International Journal of Scientific Research and Management (IJSRM), 2015)
Obesity a roaring issue of the country, vis-à-vis India. America, Australia, and many other, we seldom find those bulges in many people, and not only the bulges but really big fat piece of mass, plumping out of the waist, upper part and the lower part of the body .These days we are too much health conscious about ourselves but at the same time we are with a mindset that now can we really decrease the weight, we go to the gyms but jabber so much that we exhaust all our stamina to our best. But it becomes really mental of us when we blame food for our obesity, i.e. we blame fast food for the plumpness which we acquire, but how far it is true let us see, this paper is basically for the reason that how and why do the people bear such a mentality of how fast food effect us and up to what extent